INTEGRASI DEEP LEARNING DALAM PEMBELAJARAN BERBASIS PROYEK PADA PENDIDIKAN ANAK USIA DINI (PAUD) KECAMATAN SUMBER KABUPATEN CIREBON - Nursyahidah, Nida; Sopiah, Cucu; Fauzi Rachmat, Irfan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early Childhood Education (PAUD) faces challenges in implementing active learning that promotes deep student engagement. Teacher-centered and memorization-based promotes deep student engagement. Teacher-centered and memorization-based practices continue to dominate, limiting the development of deep learning. In Cirebon Regency, Limited teacher training and reliance on worksheets hinder meaningful learning implementation. This study aimed to describe the integration of deep learning within Project-Based Learning (PJBL) at TK Lab School Universitas Muhammadiyah Cirebon. A qualitative phenomenological approach was employed in April 2026 involving Early Childhood Education teachers, the school principal, and students. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles & Huberman model concisting of data reduction, data display, and conclusion drawing, supported by prolonged observation for credibility. Findings indicated that deep learning integration in PJBL was implemented though minful learning, meaningful learning, and joyful learning. Students actively participated, connected learning with daily experiences, and demonstrated improved critical thingking and creativity. Teachers acted as facilitators and designers of innovative learning media. This approach proved effective in creating meaningful learning experiences while supporting cognitive, sosio-emotional, collaborative, and responbility development among young learners